2020
DOI: 10.18683/germs.2020.1202
|View full text |Cite
|
Sign up to set email alerts
|

Molecular study of human astrovirus in Egyptian children with acute gastroenteritis

Abstract: Introduction Human astrovirus (HAstV) has been increasingly identified as an important cause of acute gastroenteritis in young children. Limited information is available about the prevalence and genotype distribution of classic HAstV causing acute gastroenteritis in Egyptian children.Methods Stool samples were collected from 100 infants and children attending the gastroenterology outpatient clinic in Mansoura University Children Hospital and suffering from acute gastroenteritis during the period extending from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Among the 100 studied children with AGE, norovirus and astrovirus were detected in 27% and 12%, respectively. These prevalence rates were similar to previous studies from Egypt [ 32 ], the Republic of Congo (10.3%) [ 33 ], and India (12.5%) [ 34 ]. Nevertheless, the rates were higher than reported in a previous study from Kenya (6.3%) [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among the 100 studied children with AGE, norovirus and astrovirus were detected in 27% and 12%, respectively. These prevalence rates were similar to previous studies from Egypt [ 32 ], the Republic of Congo (10.3%) [ 33 ], and India (12.5%) [ 34 ]. Nevertheless, the rates were higher than reported in a previous study from Kenya (6.3%) [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of these viruses was lower than others obtained in Egypt (28%) and Nigeria (40.4%) [ 36 , 37 ]. The variation in the prevalence rates can be attributed to the difference between geographical regions and the difference in socioeconomic factors [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The astrovirus rate in this study was 11.7%. The presence of astrovirus was investigated by El Sayed Zaki et al 23 by RT-PCR in 100 children with AGE in Egypt, and it was found at a rate of 11.1% consistent with this study. In the study of Lekana-Douki et al investigating the molecular epidemiology of gastroenteritis viruses in children under 5 years old in Gabon, astrovirus was detected to be 6.3%.…”
Section: Discussionsupporting
confidence: 87%
“…The dry conditions in rural areas can lead to increased water storage which then increases the risk of water contamination, as well as less water accessible for personal hygiene, which increases the risk of potential diseases [ 2 , 26 ]. Virus detection may have been influenced by seasonality; Sapovirus and Rotavirus are more prevalent in cold months [ 72 , 73 ], while Astrovirus infections are more likely to occur in spring and summer [ 74 ]. In the current study, Norovirus was more prevalent in specimens collected from patients presenting with diarrhoea during the rainy season, and this is consistent with previous studies [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%